Information modelling and knowledge bases XXI - Welzer, Tatjana, 1961- (IOS Press, 2010)
Drawing together researchers and practitioners from the field, European-Japanese conferences aim to advance research into, and the application of, information modelling and knowledge bases. This title contains papers presented at the 19th European-Japanese Conference on information modelling and knowledge bases (EJC 2009).
Keywords: Information modeling -- Congresses.; System design -- Congresses.; Expert systems (Computer science) -- Congresses.; Modèles d'information -- Congrès.; Conception de systèmes -- Congrès.; Systèmes experts (Informatique) -- Congrès.; Expert systems (Computer science); Information modeling; System design; Conference papers and proceedings